Reformulating Sentencing for Perpetrators of Sexual Violence Against Minors Within the Family in A Fair Manner in Indonesia - Muhammad Zakir; M. Imam Santoso; Parbuntian Sinaga; Hartanto Hartanto (Ridwan Institute, 2026)
Sexual violence against children committed by family members constitutes a serious crime that not only violates criminal law but also undermines the fundamental role of the family as a space for protection, care, and child development. Although Indonesia has established various legal instruments, including the Child Protection Act (Law No. 35 of 2014) and the Sexual Violence Crimes Act (Law No. 12 of 2022), the prosecution of perpetrators of intra-family sexual violence still tends to fail in providing an optimal deterrent effect. Furthermore, the handling of these cases has not been fully oriented toward the best interests of the child, particularly in relation to victim protection, recovery, and the prevention of revictimization throughout the criminal justice process. This study employed a normative-empirical legal research method using statutory, conceptual, and case approaches, supported by empirical data obtained through interviews with stakeholders involved in child protection and law enforcement. The findings indicate that sentencing decisions often fail to adequately consider family-based power relations, the long-term traumatic effects experienced by child victims, and the potential risk of revictimization. In addition, the weak integration between primary penalties, additional penalties, and child protection mechanisms demonstrates that the existing penal system has not yet provided substantive justice for victims. This study recommends reforming sentencing policies by developing a fairer sentencing model that prioritizes victim protection. The proposed reform includes increasing the additional penalty enhancement to one-half of the principal sentence, replacing the current one-third increase, for perpetrators of intra-family sexual violence.